A Study on the Relationship between Indian Parents’ Education Level and Their Involvement in Their Children’s Education - Suresh Kumar N. Vellymalay (Kajian Malaysia, 2011)
This study was designed to identify the relationship between Indian parents' education level and their involvement in their children's education. In total, 150 Indian students studying in National Schools in the district of Kerian, Perak Darul Ridzuan, were randomly chosen using stratified random sampling. The sample comprised 50 students from Year Three, 50 students from Year Four and 50 students from Year Five. Structured interviews were conducted with the respondents. Questionnaires were used by the researcher to obtain quantitative data related to the parents' socioeconomic background, the parents' involvement and the strategies the parents implemented for involvement in their children's education. The findings of the study indicate a moderate relationship between the parents' education level and the strategies the parents implemented. The higher the standard of parents' education, the higher the educational aspirations held by the parents regarding the academic achievement of their children. In addition, parents with a higher level of education tend to utilise various strategies of involvement at home and at school to foster academic excellence in their children.